Influencia del canon petrolero del Gobierno Regional de Loreto sobre la actividad empresarial durante los años 2011 al 2016 - Gómez Tuesta, Luis (2024)
The general objective of this work was to determine to what extent the presence and variations of income from oil canon and overcanon to the Loreto region influenced regional economic dynamism in the interval from 2011 to 2016. It was a quantitative aproach, descriptive, and correlational level with a non-experimental design, with a universe of all the companies in Loreto as a secondary source and 125 businesses for a survey as a primary source. A flow of annual income was found due to oil canon and overcanon with an interval rate of -21.70 million soles per year. Most of the indicators yielded results that describe some level of inverse correlation, that is, while income from canon and overcanon decreased, economic, employment, financial results, visitor flow, tax collection, business opening, Gross Added Value, etc. results grew. It is the narrative of a gap in economic theories in the study interval and a response to the experience of a region that can escape the phenomenon called “curse of natural resources.” A very frequent characteristic found in the study was that the statistical significance yielded was p>0.05, which indicates that the results of business development have not necessarily been influenced by oil canon and overcanon but by other random factors. Apart from oil production, the most productive economic activities were trade and general services. Those with the highest correlation with oil canon and overcanon were activities in electricity-gas-water, construction, and telecommunications.